Komunikat z badania postaw młodzieży wobec wyborów parlamentarnych 2007 roku na przykładzie uczniów klas trzecich Liceum Ogólnokształcącego w Opalenicy - Lebiotkowski, Andrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
Method of diagnostic poll was applied in the survey of youth attitudes at the Opalenica Senior High School. Out of the overall population of the Comprehensive High School Complex, day students of the last year of senior high school were selected. These were the students who could take part in the parliamentary election for the first time in 2007, that is who enjoyed suffrage rights. The survey was conducted on October 17, 2007.